2018
DOI: 10.3389/fpsyg.2018.02580
|View full text |Cite
|
Sign up to set email alerts
|

Can Touchscreen Devices be Used to Facilitate Young Children's Learning? A Meta-Analysis of Touchscreen Learning Effect

Abstract: Because of the continuous stream of touchscreen apps that are claimed to be educational and the increasing use of touchscreen devices in early childhood, considerable attention is being paid to the effect of touchscreens on young children's learning. However, the existing empirical findings in young child samples are not consistent. In this meta-analysis we tested the overall effect of touchscreen devices on young children's (0- to 5-year-olds) learning performance, as well as moderators of this effect, based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 92 publications
2
43
0
Order By: Relevance
“…15,16 In one recent metaanalysis, authors reported a significant positive effect across studies of young children's learning from touchscreen devices. 17 However, there was significant clinical and methodological heterogeneity in the included studies, which encompassed varied types of interventions (eg, electronic books, interactive game apps), outcomes targeted, comparison groups, and study designs (randomized and nonrandomized, controlled and noncontrolled). Statistical heterogeneity in this study was high (I 2 .90%), limiting interpretability of a meta-analytic effect size.…”
mentioning
confidence: 99%
“…15,16 In one recent metaanalysis, authors reported a significant positive effect across studies of young children's learning from touchscreen devices. 17 However, there was significant clinical and methodological heterogeneity in the included studies, which encompassed varied types of interventions (eg, electronic books, interactive game apps), outcomes targeted, comparison groups, and study designs (randomized and nonrandomized, controlled and noncontrolled). Statistical heterogeneity in this study was high (I 2 .90%), limiting interpretability of a meta-analytic effect size.…”
mentioning
confidence: 99%
“…While the current study makes a valuable contribution to an emerging evidence based on the impact of educational touchscreen apps on child development (Herodotou, 2018;Xie et al, 2018), five issues should be considered in directing future research. First, it is important to recognize that this study has been conducted in Malawi, where children's access to tablet technology is largely limited to education and only in a few schools.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…An emerging evidence base demonstrates the potential for educational touchscreen applications (apps) to support the development of domain-specific mathematical knowledge (Herodotou, 2018;Xie et al, 2018). In particular, a randomized control trial (RCT) conducted in Malawi found children in the first 3 years of primary school made significantly greater mathematical learning gains when using hand-held touch-screen tablets with an interactive, child-centered maths app, compared to standard teacher-led mathematical practice (Pitchford, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As interactivity has been found to complement the preferred learning style of children (Highfield and Goodwin 2013), it is hypothesised that both populations in the interactive condition will exhibit greater on-task engagement for both engagement measures (visual attention and communication) compared to the 2D and automatic conditions. Finally, based on previous research we expect greater engagement to be contingent symbolic understanding and label retention after a delay (Kucirkova 2014;Radesky et al 2015;Xie et al 2018).…”
mentioning
confidence: 99%